MODIFIABLE AND NON-MODIFIABLE RISK FACTORS FOR TUBERCULOSIS AMONG ADULTS IN INDONESIA: A SYSTEMATIC REVIEW AND META-ANALYSIS - Ricvan Dana, NINDREA; Rika, SUSANTI; Pudia M, INDIKA; Benny Alexander, MAISA; Muthia, SUKMA; Linda, ROSALINA; Astri, WIDYA; Zuhrah, TAUFIQA; Dede Rahman, AGUSTIAN; Rahmi, FITHRIA; Nomira, PUTRI; Dianni Arma Wahyu Setia, NINGSIH; et al. (African Journal of Infectious Diseases (AJID), 2024)
Background: Controlling tuberculosis (TB) determinant factors in Indonesia is one way TB control in the community. A review is needed to explore risk factors for TB in Indonesia as the key strategies for accelerating the TB preventive program. Aim: The purpose of this review was to determine modifiable and non-modifiable risk factors for TB among adults in Indonesia. Methods: A meta-analysis was undertaken to review current studies related to modifiable and non-modifiable risk factors for TB among adults in Indonesia. A search of PubMed, ProQuest, and Google Scholar for related articles published (January 2000 until December 2023). The Pooled Odds Ratio (POR) from the acquired data was calculated with a 95% CI. The fixed and random effects analysis was performed. The results were presented as forest plots, and Egger's test was used to examine study bias. Review Manager (RevMan) 5.4 and Stata 14.2 were used to process and analyze all of the data. Results: This study results revealed the POR of non-modifiable risk factors (family history of TB) for TB among adults in Indonesia was 6.08 (95% CI 2.99-12.34). Based on modifiable risk factors, it is known household contact has the highest POR (6.01, 2.57-14.04), followed by malnutrition (5.86, 2.50-13.69), inappropriate ventilation (5.57, 1.74–17.86), diabetes mellitus (4.92, 3.04-7.96), smoking behavior (3.24, 2.22-4.72), and low-income level (2.34, 1.42-3.87). Conclusion: Based on significant factors that are related to TB incidence, the results of this review may be valuable to the government in identifying the optimal strategy for TB prevention among adults.